Mir-221/222 are promising targets for innovative anticancer therapy. (1st September 2016) - Di Martino, Maria Teresa; Rossi, Marco; Caracciolo, Daniele; Gullà, Annamaria; Tagliaferri, Pierosandro; Tassone, Pierfrancesco
ABSTRACT: Introduction : MicroRNAs (miRNAs) are key non-coding RNA post-transcriptional regulators of messenger RNAs (mRNAs), and are deeply dysregulated in human cancer. A rising body of evidence indicates that miRNAs represent valuable therapeutic targets. In this light, the cluster miR-221/222 are of particular relevance, given that they are strongly upregulated in a variety of solid and hematologic malignancies. Area covered : This review summarizes recent findings on the roles played by miR-221/222 in human cancer and their potential clinical value as promising targets for therapeutic studies. Expert opinion : The rising body of advanced preclinical evidence on the biological significance of miR-221/222 in a variety of malignancies indicates that they will play a crucial role in the future of innovative therapeutic strategies, both as validated biomarkers and targets.